Analisis perbandingan PSAK 55 dan PSAK 71 pada PT bank negara indonesia (persero) Tbk - Aulia Fatiha Kurniadi; Lathifah Ayu Rahmanissa; Leila Hasnah Rosydah; Putri Astari Angraini; Yolanda Rudila Putri (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2022)
This study aims to examine the comparison of PSAK 55 and PSAK 71 and their impact and implementation on PT Bank Negara Indonesia (BNI) Tbk. The descriptive qualitative method which is explanatory research with a literature study approach and content analysis is the research method used. In this study, secondary data is the data used which takes data and information from the annual financial statements of Bank BNI sourced from the BEI website. The results of the study are the impact of the enactment of PSAK 71 which lies in the measurement and grouping of financial assets, as well as the calculation of CKPN which was originally calculated based on historical data to be forward looking.